PERBUATAN MEMBERIKAN GANJA KEPADA ORANG LAIN SEBAGAI ALTERNATIF PENGOBATAN DITINJAU DARI SIFAT MELAWAN HUKUM DALAM HUKUM PIDANA (STUDI KASUS FIDELIS ARIE SUDEWARTO) - Maria Tarigan; Nathalina Naibaho (Faculty of Law, Universitas Riau, 2020)
The use of marijuana in medication has been criminalized in Indonesia since 1997. Twenty years after, Fidelis Arie Sudewarto violated the rule by administering marijuana as an alternative means of medication for his spouse, Yeni Riawati. Various public opinions emerged, indicating a shift of paradigm on the use of marijuana for medication, and this affects the fulfillment of